PPKn Teacher Strategy In Planting Tolerance and Diversity In School Intermediate Vocational Islamic Center of Sigi Regency - Irawati Mole; Amus, Sunarto; Hasdin (Kirana Publisher (KNPub), 2025)
Education is component main in life human . Through education , human can more develop knowledge and skills , improve quality life , and can know himself themselves . Moral degradation occurs due to from internal factors and external factors external . Formulation problem study What is the strategy of PPKn teachers ? to plant tolerance at Islamic Center Vocational School Sigi Regency , Effectiveness from the PPKn teacher strategy in to plant tolerance at Islamic Center Vocational School Sigi Regency . Research objectives This is strategy and effectiveness from the PPKn teacher strategy in to plant tolerance at Islamic Center Vocational School Sigi Regency . Approach method qualitative that is For process the data obtained from location study Where the data in the form of words, sentences , schemes or image . Referring to the concept used , namely For know and understand the PPK Teacher Strategy n in to plant Tolerance and Diversity at Islamic Center Vocational School Sigi Regency . The results of the Strategy research provide unity directionforshare all member organization . If the concept of strategy No clear , then decision which is taken will nature subjective or based on intuition alone and ignore other decisions. Strategy can interpreted as tool For reach objective long-term . Strategy is action potential need decision managementlevel above and resources companyin a large number .